2005
DOI: 10.1002/jso.20270
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT criteria in predicting survival in patients with potentially resectable pancreatic head carcinoma

Abstract: CT signs of local irresectability and a tumor diameter of >3 cm predict a poor survival after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…As of now, the sensitivity and specificity of the assessment of vascular involvement, even with a > 90 o circular contact and marked vascular deformity (D or E according to Phoa), are reported at 60% and 90% correspondingly [62,63] , which indicates that the accuracy of pancreatic cancer resectability appraisal is an elusive troublesome question. Based on the findings reported by various researchers, Li et al [64] defined the following CT criteria for major vascular invasion with an exhibited sensitivity of the method of 79% and a specificity of 99%: embedment of the arterial trunk in tumor, encasement by tumor > 180 o or > 50% of the vessel circumference coupled with either irregularity of the wall contour or arterial narrowing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As of now, the sensitivity and specificity of the assessment of vascular involvement, even with a > 90 o circular contact and marked vascular deformity (D or E according to Phoa), are reported at 60% and 90% correspondingly [62,63] , which indicates that the accuracy of pancreatic cancer resectability appraisal is an elusive troublesome question. Based on the findings reported by various researchers, Li et al [64] defined the following CT criteria for major vascular invasion with an exhibited sensitivity of the method of 79% and a specificity of 99%: embedment of the arterial trunk in tumor, encasement by tumor > 180 o or > 50% of the vessel circumference coupled with either irregularity of the wall contour or arterial narrowing.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the findings reported by various researchers, Li et al [64] defined the following CT criteria for major vascular invasion with an exhibited sensitivity of the method of 79% and a specificity of 99%: embedment of the arterial trunk in tumor, encasement by tumor > 180 o or > 50% of the vessel circumference coupled with either irregularity of the wall contour or arterial narrowing. Loyer et al [65] established that with type A (a fat plane between tumor and vessel) or type B (a normal pancreatic parenchyma separating the tumor from the vessel), the accuracy of the resectability prediction was 95% and Phoa et al [62] showed type D (a vascular wall concavity against the tumor to be consistent with a 88% risk for invasion and a 7% predicted resectability) and type E (complete vascular encirclement by tumor) to correlate with a 0% resectability, depending on tumor surface irregularity and vascular deformity. Nevertheless, there is presently no consensus of opinion as to the modality of choice for the assessment of pancreatic cancer extension previous to surgery, since studies that would offer sufficient accuracy are lacking [66,67] .…”
Section: Discussionmentioning
confidence: 99%
“…This shows the improvement in prediction of resectability by MDCT. [6][7][8][17][18][19]25,26 The common reason for unresectability was vascular invasion, local spread and metastases. In the present study MDCT yielded a NPV of 90.3% for detecting vascular invasion and local spread, and NPV of 96.8% for detecting abdominal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing resection, a diameter > 2 cm on pre-operative imaging is an independent factor of poor prognosis (relative risk of death = 3.2, p = 0.05). Other predictive signs of poor prognosis on pre-operative imaging include convex tumor shape and vascular invasion [26]. Several hypotheses can be advanced to explain the negative impact of large tumor size on survival [25].…”
Section: Discussionmentioning
confidence: 99%